2013
DOI: 10.1245/s10434-013-3401-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Profiling Identifies EYA4 Gene as a Prognostic Molecular Marker in Hepatocellular Carcinoma

Abstract: EYA4 functions as a prognostic molecular marker in HCC. Its aberrant hypermethylation and subsequent down-regulation may promote tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…Thus, we sought to study its role in ESCC. Numerous studies have indicated that EYA4 is aberrantly expressed in a variety of cancers, such as hepatocellular carcinoma, intrahepatic cholangio‐carcinoma, colorectal cancer and acute lymphoblastic leukemia . Consistent with these findings, in the present study, we found that EYA4 was aberrantly hypermethylated in both ESCC specimens and cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we sought to study its role in ESCC. Numerous studies have indicated that EYA4 is aberrantly expressed in a variety of cancers, such as hepatocellular carcinoma, intrahepatic cholangio‐carcinoma, colorectal cancer and acute lymphoblastic leukemia . Consistent with these findings, in the present study, we found that EYA4 was aberrantly hypermethylated in both ESCC specimens and cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have indicated that EYA4 is aberrantly expressed in a variety of cancers, such as hepatocellular carcinoma, intrahepatic cholangio-carcinoma, colorectal cancer and acute lymphoblastic leukemia. 16,[19][20][21][22] Consistent with these findings, in the present study, we found that EYA4 was aberrantly hypermethylated in both ESCC specimens and cell lines. Then, we assessed the expression of EYA4 in ESCC cell lines and found that reduced EYA4 expression in 6 of 7 ESCC cell lines was associated with methylation status.…”
Section: Discussionsupporting
confidence: 91%
“…; *, p<0.05. Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry one of the EYA family members, has been reported to play an important role in various cancers [11,12,33,34]. In this study, we found that EYA4 was upregulated in glioma and its levels were positively correlated with advanced tumor stage, which was consistent with its previously reported roles in other cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, EYA4 protein levels were lower in CCA patients with lymph node metastasis, and low expression of EYA4 was an independent prognostic factor for overall and disease-free survival 117 . Of note, EYA4 down-regulation in CCA tissue might result from gene promoter hypermethylation, as reported in other cancer types 118,119 . Although the precise antitumor function played by EYA4 in CCA requires further exploration, it is worth noting that in colorectal cancer, EYA4 keeps at bay the pro-neoplastic Wnt signaling by stimulating DKK1 expression 119 .…”
Section: Novel Signaling Mechanisms and Trascription Factors Promotinmentioning
confidence: 54%